WIDER INFLUENCE OF VOLUNTARY DISCLOSURE AND QUALITY OF INCOME ON COST OF CAPITAL - Yolifiandri (Journal of Research in Business, Economics, and Education, 2019)
For companies in Indonesia that have gone public or registered in the capital market are required to submit information about the company's activities in the form of financial reports and annual reports. Companies listed on the capital market are expected to be more transparent in disclosing their company's financial information. The information asymmetry that occurs between managers and shareholders as users of financial statements causes shareholders to not be able to observe the company's overall performance and prospects perfectly. In situations where shareholders have less information than managers, managers can take advantage of the flexibility they have to carry out earnings management. Based on the results of the analysis and discussion in this study, the conclusion is voluntary disclosure, asymmetry of information produces an insignificant negative direction on the cost of equity capital, while for earnings management variables produce a positive and insignificant relationship to the cost of equity capital. This is because investors consider that at this time, issuers or companies that issue new common shares are covering their operational and investment debts, so the company is less interested in investors.